Styles of educational management and teaching performance at the Saco Oliveros - Lima Educational Institution, 2018 - Quispe Sánchez, Norma (2019)
The objective of this research is to determine in what extent the styles ofEducational Management of the managers in the educational institution SacoOliveros are related to the Teaching Performance. The study by its nature is ofa quantitative nature, it is basic non-experimental cross-correlation, whosepurpose is to measure the degree of relationship between the dimensions ofboth variables. The population is composed of 3 directors, 27 teachers and 269students.